Influence of Stress and Depression on the Immune System in Patients Evaluated in an Anti-aging Unit - Cañas-González, Beatriz; Fernández-Nistal, Alonso; Ramírez, Juan M.; Martínez-Fernández, Vicente (Frontiers in Psychology, 2020)
Background. There is compelling evidence pointing out that stress and depression produce a dramatic impact on human wellbeing mainly through impairing the regular function of the immune system and producing a low-chronic inflammation status that favors the occurrence of infections, metabolic diseases and even cancer. The present work aims to evaluate the stress/depression levels of some patients treated in an anti-aging unit and detect any potential relationship with their immune system status, prior of the implementation of a physical/psychological program designed to prevent health deterioration. Methods. We evaluated 48 patients (16 men and 32 women with a mean of 55.11±10.71 years old) from middle-upper class from psychological and immunological points of view. In particular, we analyzed neutrophil chemotaxis and phagocytosis; lymphocyte chemotaxis and proliferation and natural killer cells activity. Results: Woman showed more depressive symptoms than men. Chemotaxis levels of lymphocytes and neutrophils in women showed a significant reduction compared with that on men. We also found a strong negative correlation between depression and natural killer cell function. This correlation was also significant independently of gender. Conclusions: We conclude that natural killer activity is affected at least by depression state and we propose that a combined treatment consisted in cognitive behavioral therapy and physical activity programs might improve patient health deterioration.